Abdominal obesity and cardiometabolic risk in children and adolescents, are we aware of their relevance?. Issue 1 (December 2016) - Forkert, Elsie; Rendo-Urteaga, Tara; Nascimento-Ferreira, Marcus; de Moraes, Augusto; Moreno, Luis; de Carvalho, Heráclito
Abstract Obesity prevalence has increased worldwide over the last decades and has reached alarming rates in low middle-income countries. Childhood has been affected by this epidemic, leading to premature dramatic health problems. Adipose tissue is currently considered as an endocrine organ modulating an inflammatory state and important metabolic processes (insulin resistance, hypertension, glucose intolerance) leading to consequences of the cardiovascular system. This situation may be worst if the excess of body fat distribution such as abdominal obesity (AO) is involved because it is associated with a more atherogenic risk profile determining the cardiometabolic risks mainly in children and adolescents. Hence, the knowledge regarding the association between AO and cardiometabolic factors aims to prevent and treat the obesity in this young population, avoiding early harmful consequences of adulthood health.